Silicon Isotope Signatures of Radiolaria Reveal Taxon-Specific Differences in Isotope Fractionation - Doering, Kristin; Ehlert, Claudia; Pahnke, Katharina; Frank, Martin; Schneider, Ralph; Grasse, Patricia (Frontiers in Marine Science, 2021)
The global silicon (Si) cycle plays a critical role in regulating the biological pump and the carbon cycle in the oceans. A promising tool to reconstruct past dissolved silicic acid (DSi) concentrations is the silicon isotope signature of radiolaria (δ30Sirad), siliceous zooplankton that dwells at subsurface and intermediate water depths. However, to date, only a few studies on sediment δ30Sirad records are available. To investigate its applicability as a paleo proxy, we compare the δ30Sirad of different radiolarian taxa and mixed radiolarian samples from surface sediments off Peru to the DSi distribution and its δ30Si signatures (δ30SiDSi) along the coast between the equator and 15°S. Three different radiolarian taxa were selected according to their specific habitat depths of 0–50 m (Acrosphaera murrayana), 50–100 m (Dictyocoryne profunda/truncatum), and 200–400 m (Stylochlamydium venustum). Additionally, samples containing a mix of species from the bulk assemblage covering habitat depths of 0 to 400 m have been analyzed for comparison. We find distinct δ30Sirad mean values of +0.70 ± 0.17‰ (Acro; 2 SD), +1.61 ± 0.20 ‰ (Dictyo), +1.19 ± 0.31 ‰ (Stylo) and +1.04 ± 0.19 ‰ (mixed radiolaria). The δ30Si values of all individual taxa and the mixed radiolarian samples indicate a significant (p < 0.05) inverse relationship with DSi concentrations of their corresponding habitat depths. However, only δ30Si of A. murrayana are correlated to DSi concentrations under normally prevailing upwelling conditions. The δ30Si of Dictyocoryne sp., Stylochlamydium sp., and mixed radiolaria are significantly correlated to the lower DSi concentrations either associated with nutrient depletion or shallower habitat depths. Furthermore, we calculated the apparent Si isotope fractionation between radiolaria and DSi (Δ30Si ∼ 30ε = δ 30Sirad − δ 30SiDSi) and obtained values of −1.18 ± 0.17 ‰ (Acro), −0.05 ± 0.25 ‰ (Dictyo), −0.34 ± 0.27 ‰ (Stylo), and −0.62 ± 0.26 ‰ (mixed radiolaria). The significant differences in Δ30Si between the order of Nassellaria (A. murrayana) and Spumellaria (Dictyocoryne sp. and Stylochlamydium sp.) may be explained by order-specific Si isotope fractionation during DSi uptake, similar to species-specific fractionation observed for diatoms. Overall, our study provides information on the taxon-specific fractionation factor between radiolaria and seawater and highlights the importance of taxonomic identification and separation to interpret down-core records.